The influence of service quality towards tourist satisfaction: Melaka Duck Tours / Syahira Farzana Shaharruzzaman , Nurul Fathiah Zainal and Mohd Firdaus Abd Aziz - Shaharruzzaman, Syahira Farzana; Zainal, Nurul Fathiah; Abd Aziz, Mohd Firdaus (Faculty of Hotel and Tourism Management, 2013)
In the highly competitive tourism industry, improving service quality to gain competitive advantages is very important in order to remain competitive in tourism business and hence grow. It is very important for service provider to know how to measure these constructs from the tourists' perspective in order to better understand their needs and hence satisfy them. Service quality is considered very important because it leads to higher customer satisfaction, profitability and lead to sustainable management of tourist attractions. Tourist satisfaction is recognized as one of the key judgments that tourists use to measure tourism services. This study examined the relationship between service quality and tourist satisfaction of tourists that have experienced Melaka Duck Tours using SERVQUAL model and analyzed which dimension of service quality that most influenced the tourist satisfaction using multiple regression analysis. This field research was conducted at the Melaka Duck Tours. The model was tested using data collected from 50 tourists. The results revealed that service quality has a positive relationship on tourist satisfaction. The result of this study also revealed that tangible was the most influencing dimension of service quality. The results also provide potential guidelines for Melaka Duck Tours management to be able to retain the quality of service that is considered satisfactory by the tourists and will improve the quality of services that are deemed less satisfactory by the tourists.